THE ROLE OF SERUM AND URINARY CALCIUM LEVELS IN RENAL LITHIASIS - Khan, Shaheen Pervez; Shahjahan, Syed (Journal of Ayub Medical College Abbottabad, 1998)
Serum and urinary calcium levels play a major role in the aetio-pathogenesis of renal stone formation. In this study, serum and 24 hours' urinary calcium of 30 healthy controls and 60patients of renal lithiasis were studied. The mean age of controls and patients was 34.9 (range 3-60 years) and 37.5 years (range 3 to 70 years) respectively. The male to female ratio of controls and patients was 1.6:1 and 1.5:1 respectively. Chemical analysis of stones showed 42 (70.0%) were pure calcium oxalate, 2 (3.3%) pure uric acid, while the others were mixed stones. Calcium was found in 58 (96.7%) stones. The overall mean + SE of serum calcium among the controls and patients was 9.43 ± 0.14 and 9.46 ± 0.15 respectively, which is statistically not significant. Although the overall values of calcium of controls and patients was similar, its distribution of concentration showed that 1(3.3%) control and J1 (18.3%) patients were hypercalcemic, while 4 (13.3%) controls and 19(31.7%) patients were found hypercalciuric. Idiopathic hyper-calciuria was found in 3(10%) of controls as compared to 8(13.3%) patients. As hypercalciuria is the more common laboratory finding compared to hypercalcemia among these renal stone patients, so routine screening of 24 hours' urinary calcium is valuable in diagnosis and aetiology of calcium-containing renal stones.